Religion and democratisation: what do we now know? - Haynes, Jeffrey (Journal of religious and political practice, 2016)
Democratisation is a process of moving from an authoritarian regime to a democratic state. A democratic state has its governance rooted in representative institutions, with officeholders chosen by the populace through periodic "free and fair" local and national elections. The relationship between religion, democratisation and democracy centres on three issues:. Religious traditions have core elements: some are conducive to democratisation and democracy, others less so;. Religious traditions are typically multi-vocal: at any moment there will be powerful figures more or less receptive to and encouraging of democracy;. Religious actors on their own rarely if ever determine democratisation outcomes. Yet, they may in various ways and with a range of outcomes be significant for democratisation. This may especially be the case in countries that have a long tradition of secularisation, such as Turkey. This introductory article examines these issues and uncovers the significant links between religion and democratisation, relating them to the other contributions in this special issue.